The Investigation on Preparation of Nano-Sized Raw Medicinal Material from the Natural Spar - Oyun, J (Proceedings of the Mongolian Academy of Sciences, 2011)
In the result of many years’ investigations we have developed a new version of medical mineral processing technology based on the Mongolian traditional technology. By this technology a nano-sized raw medicinal material has been derived from medical quality natural minerals without involving any kind of chemical reagents and grinder. The size, composition and structure of the resultant product are confirmed by CT microscope, IR spectrometer and X-ray refractometer analysis as being 98% calcium hydrate (Ca(OH2)) containing 13.09 nm lutetium, bounded with milk protein and amino-acid, and is being transformed to the co-ferment (metal-organic) form of 13.51 nm nano-cluster lactate calcium. This work is the kind of first in the field of nano-technology development in Mongolia and therefore describes some parts of investigations carried out for the derivation of nano-sized new raw medicinal material in more detail. DOI: http://dx.doi.org/10.5564/pmas.v0i4.52 Proceedings of the Mongolian Academy of Sciences 2009 No.4 pp.90-100